An Innovative Design of Magnetorheological Lateral Damper for Secondary Suspension of a Train - Masa'id, Aji; Ubaidillah, Ubaidillah; Lenggana, Bhre; Muhayat, Nurul; Wibowo, Wibowo; Mazlan, Saiful (http://dx.doi.org/10.31427/IJSTT.2019.2.2.2, 2019)
This article delivered an innovative idea of a magnetorheological (MR) damper for secondary suspension of train bogie. The valve inside MR damper adopted meandering of both fluid flow and magnetic flux for improving magnetization area. In this work, the design and working principle of the MR valve were presented including a mathematical model to predict the pressure drop. In the early stage, the finite element method magnetics software (FEMM) simulation could predict the magnetic flux density across the passages. Based on the amount of magnetic flux, the corresponding shear yield stress could be determined from its basic physical properties. The mathematical model covered pressure drop prediction for both off-state and on-state. The FEMM simulation results showed that the meandering flow and serpentine flux design could improve the effective area of magnetization. Consequently, the pressure drop of the valve could have wider ranges and achieve a high value of pressure differences. This result could be potentially improving the performance of the damping forces of the lateral damper in a bogie train.